2010
DOI: 10.2340/16501977-0609
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of a 20-week whole-body vibration training programme on leg muscle performance and function in persons with multiple sclerosis

Abstract: Under the conditions of the present study, the applied 20-week whole-body vibration exercise protocol did not improve leg muscle performance or functional capacity in mild- to moderately impaired persons with multiple sclerosis during and immediately after the training programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 40 publications
4
76
0
1
Order By: Relevance
“…9 The effects of WBV training on gait performance in persons with Parkinson's disease and adults with cerebral palsy are also reported to be small and not more efficient than conventional training. 10,12 In persons with Multiple Sclerosis, 20 weeks of WBV training did not have any effects on leg muscle performance and functional capacity 28 as compared to controls maintaining their usual lifestyle. Thus, studies so far have not been able to show that WBV training is a viable treatment for patients with stroke or other neurological disorders.…”
Section: Discussionmentioning
confidence: 94%
“…9 The effects of WBV training on gait performance in persons with Parkinson's disease and adults with cerebral palsy are also reported to be small and not more efficient than conventional training. 10,12 In persons with Multiple Sclerosis, 20 weeks of WBV training did not have any effects on leg muscle performance and functional capacity 28 as compared to controls maintaining their usual lifestyle. Thus, studies so far have not been able to show that WBV training is a viable treatment for patients with stroke or other neurological disorders.…”
Section: Discussionmentioning
confidence: 94%
“…Vibration platforms are more and more often used in rehabilitation centers for patients with MS, although the results of research studies have not unequivocally confirmed the effectiveness of WBV in those patients (8). Individuals with mild to moderate impairment were enrolled in these studies; Expended Disability Status Scale scores were 4. training, and pool therapy, WBV is now comprised in a new physiotherapy concept "On your feet" used in children with bilateral spastic cerebral palsy.…”
Section: Nervous System Diseasesmentioning
confidence: 99%
“…Despite being on the market for over a decade and tested in different neurological disorders, there are not yet any clear results regarding positive effects of WBV training. Even though some studies have reported improvements (2,3), others have not found it to be better than traditional interventions (3)(4)(5)(6). The reported effects are usually small in comparison with other established interventions and often within the limits of normal variations or measurement errors.…”
mentioning
confidence: 99%